The Stenchaetothrips species (Thysanoptera, Thripidae) of Malaysia, with one new species - Ng, Y. F.; Mound, L. A. (Zootaxa, 2012)
Four species of Stenchaetothrips are here recorded from Peninsular Malaysia. These are S. biformis, the widespread ricethrips, S. hullikali, known only from Karnataka in Southwest India, S. indicus, a widespread species on grasses, and S.langkawiensis sp. nov., described here from Langkawi Island, West Malaysia. Species descriptions, photographs and an identification key are provided.